How the globalization and Libralisation impact the locals - Choudhury, Sabyasachi Basu Ray; Dey, Ishita; Aneet (Gyan Management Journal, 2012)
This book talks about the interconnectedness of globalization with social and economic systems and how links develop with reference to both polity and common people’s movements. Aspects like analysis of the interdependem;e of market forces, the state, and the neo-liberal economic policies and how they impact the livelihood of people, have also been analyzed in the book. The various chapters in the book contribute to a new way of understanding one’s basic rights with the help of micro-histories drawn from fields as diverse as environmental rights, law, and communication and labor studies in India. The book shows how rights have been redefined in this era of globalization and it examines how the constant tension between social yearning for democratic values and economic competition for unhindered profits, still plagues India today.